2003
DOI: 10.1177/153537020322800202
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dopamine Receptors and Hypertension

Abstract: Dopamine has been recognized as an important modulator of central as well as peripheral physiologic functions in both humans and animals. Dopamine receptors have been identified in a number of organs and tissues, which include several regions within the central nervous system, sympathetic ganglia and postganglionic nerve terminals, various vascular beds, the heart, the gastrointestinal tract, and the kidney. The peripheral dopamine receptors influence cardiovascular and renal function by decreasing afterload a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
251
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(256 citation statements)
references
References 96 publications
(132 reference statements)
2
251
0
3
Order By: Relevance
“…The D 4 receptor has abundant protein expression in the proximal tubule 3, 13. Previous studies show interactions between insulin and dopamine receptors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The D 4 receptor has abundant protein expression in the proximal tubule 3, 13. Previous studies show interactions between insulin and dopamine receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Others also showed that the interactive role of cAMP regulatory element‐binding protein and Sp1 is regulated by calcium 42. As a D 2 ‐like receptor subtype, activation of D 4 receptor increases intracellular calcium concentration 3. The present study showed that the inhibitory effect of D 4 receptor on insulin receptor expression is blocked by a calcium‐channel blocker, withdrawal of calcium in the cell culture medium, or in the presence of IP3 receptor blocker, which blocks the calcium release from endoplasmic reticulum, indicating that calcium mobilization, including extracellular calcium influx and intracellular calcium release from the endoplasmic reticulum, is involved in the signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] Several studies have reported that an impaired renal dopaminergic system may contribute to the pathogenesis of hypertension. 7,8 Dopamine receptors expressed in mammals belong to the a group of the rhodopsin family of G protein-coupled receptors. The five mammalian dopamine receptor subtypes, identified by molecular cloning, differ in their primary structures, and have distinct affinities for dopamine receptor agonists and antagonists.…”
Section: Introductionmentioning
confidence: 99%